A YWHAZ Variant Associated With Cardiofaciocutaneous Syndrome Activates the RAF-ERK Pathway - Popov, Ivan K.; Hiatt, Susan M.; Whalen, Sandra; Keren, Boris; Ruivenkamp, Claudia; van Haeringen, Arie; Chen, Mei-Jan; Cooper, Gregory M.; Korf, Bruce R.; Chang, Chenbei (Frontiers in Physiology, 2019)
Cardiofaciocutaneous (CFC) syndrome is a genetic disorder characterized by distinctive facial features, congenital heart defects, and skin abnormalities. Several germline gain-of-function mutations in the RAS/RAF/MEK/ERK pathway are associated with the disease, including KRAS, BRAF, MEK1 and MEK2. CFC syndrome thus belongs to a group of disorders known as RASopathies, which are all caused by pathogenic mutations in various genes encoding components of the RAS pathway. We recently identified novel variants in YWHAZ, a 14-3-3 family member, in individuals with a phenotype consistent with CFC that may potentially be deleterious and disease-causing. In the current study, we take advantage of the vertebrate model Xenopus laevis to analyze the functional consequence of a particular YWHAZ variant, S230W, and investigate the molecular mechanisms underlying its activity. We show that compared with wild type YWHAZ, the S230W variant induces severe embryonic defects when ectopically expressed in early Xenopus embryos. The S230W variant also rescues the defects induced by a dominant negative FGF receptor more efficiently and enhances Raf-stimulated Erk phosphorylation to a higher level than wild type YWHAZ. Although neither YWHAZ nor the variant promotes membrane recruitment of Raf proteins, the variant binds to Raf more strongly and escapes phosphorylation by casein kinase 1a. Our data provide strong support to the hypothesis that the S230W variant of YWHAZ is a gain-of-function mutation in the RAS-ERK pathway and may underlie a CFC phenotype.